2018
DOI: 10.17216/limnofish.379784
|View full text |Cite
|
Sign up to set email alerts
|

Bazı Aromatik Bitki Esansiyel Yağlarının Patojenik Balık Bakterilerine Karşı Antibakteriyel Aktivitesi

Abstract: Essential oils of twenty-four plant species were obtained by hydrodistillation and investigated for their antibacterial effects against seven fish pathogenic bacteria (Aeromonas hydrophila, Aeromonas salmonicida, Vibrio anguillarum, Yersinia ruckeri, Enterococcus faecalis, Lactococcus garvieae and Streptococcus agalactiae). The antibacterial activity results of the essential oils obtained by disc diffussion method showed strong activities against all pathogens. In general, whole essential oils except Artemisia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Rosemary and sage essential oils have been reported to be highly antimicrobial properties in numerous investigations and have also been shown to be inhibitory to pathogens (Teixeira et al, 2013). The antibacterial activity of rosemary and sage essential oils has been evaluated against major fish bacterial pathogens (Ekici et al, 2011;Mahmoodi et al, 2012;Ostrand et al, 2012;Roomiani et al, 2013;Yılmaz et al, 2013;Birinci Yıldırım and Türker, 2018). In this study, rosemary essential oil at concentration of 1000 µl ml -1 (20 mm inhibition zone) against A. sobria showed strong inhibitory effect (p<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Rosemary and sage essential oils have been reported to be highly antimicrobial properties in numerous investigations and have also been shown to be inhibitory to pathogens (Teixeira et al, 2013). The antibacterial activity of rosemary and sage essential oils has been evaluated against major fish bacterial pathogens (Ekici et al, 2011;Mahmoodi et al, 2012;Ostrand et al, 2012;Roomiani et al, 2013;Yılmaz et al, 2013;Birinci Yıldırım and Türker, 2018). In this study, rosemary essential oil at concentration of 1000 µl ml -1 (20 mm inhibition zone) against A. sobria showed strong inhibitory effect (p<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Using the same assay demonstrated that the essential oils of the flowers of lavender ( Lavandula angustifolia ), everlasting ( Helichrysum plicatum ), wormwood ( Artemisia absinthium ), leaves of pepper mint ( Mentha piperita ), sweet basil ( Ocimum basilicum ), wild marjoram ( Origanum majorana ), thyme ( Thymus vulgaris ), spiked thyme ( Thymbra spicata ), sage ( Salvia officinalis ), bay laurel ( Laurus nobilis ), lemon verbena ( Aloysia citriodora ), and seeds of black pepper ( Piper nigrum ) showed strong activity against L. garvieae strain provided by Dr. İlhan Altınok (Trabzon, Turkey), while the essential oils of flowers of French lavender ( Lavandula stoechas ), yarrow ( Achillea millefolium ), flower buds of clove ( Syzygium aromaticum ), leaves of rosemary ( Rosmarinus officinalis ), rose geranium ( Pelargonium graveolens ), parsley ( Petroselinum sativum ), river red gum ( Eucalyptus camaldulensis ), bark of cinnamon ( Cinnamomum verum ), roots of ginger ( Zingiber officinale ), and seeds of Chinese parsley ( Coriandrum sativum ) showed moderate activity, and the essential oils of leaves of common fennel ( Foeniculum vulgare ) and anise ( Pimpinella anisum ) presented weak activity [ 97 ]. Another experiment with this methodology confirmed the strong activity of the essential oil of thyme and the moderate activity of the essential oil of rosemary but stated that the essential oil of bay laurel exhibited a moderate activity against this bacterium [ 98 ].…”
Section: Phytotherapy Of Lactococcosis In Aquaculturementioning
confidence: 99%